Volatiles from the hypoxylaceous fungi Hypoxylon griseobrunneum and Hypoxylon macrocarpum - Rinkel, Jan; Babczyk, Alexander; Wang, Tao; Stadler, Marc; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2018)
The volatiles emitted by the ascomycetes Hypoxylon griseobrunneum and Hypoxylon macrocarpum (Hypoxylaceae, Xylariales) were collected by use of a closed-loop stripping apparatus (CLSA) and analysed by GC–MS. The main compound class of both species were polysubstituted benzene derivatives. Their structures could only be unambiguously determined by comparison to all isomers with different substitution patterns. The substitution pattern of the main compound from H. griseobrunneum, the new natural product 2,4,5-trimethylanisole, was explainable by a polyketide biosynthesis mechanism that was supported by a feeding experiment with (methyl-2H3)methionine.
Keywords: constitutional isomerism; gas chromatography; mass spectrometry; natural products; volatiles

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2017)

(untitled) - Kimura, M.; Tokai, T.; Takahashi-Ando, N.; Ohsato, S.; Fujimura, M. (Biosci., Biotechnol., Biochem., 2007)

(untitled) - Wei, C.-M.; McLaughlin, C. S. (Biochem. Biophys. Res. Commun., 1974)

(untitled) - Riclea, R.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2015)

(untitled) - García-Estrada, C.; Martín, J.-F. (Appl. Microbiol. Biotechnol., 2016)

(untitled) - Jeleń, H. H. (J. Agric. Food Chem., 2002)

(untitled) - Murahashi, S. (Sci. Pap. Inst. Phys. Chem. Res. (Jpn.), 1938)

(untitled) - Zawirska-Wojtasiak, R. (Food Chem., 2004)

(untitled) - Kandasamy, D.; Gershenzon, J.; Hammerbacher, A. (J. Chem. Ecol., 2016)

(untitled) - Citron, C. A.; Junker, C.; Schulz, B.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Collins, R. P.; Halim, A. F. (J. Agric. Food Chem., 1972)

(untitled) - Wickel, S. M.; Citron, C. A.; Dickschat, J. S. (Eur. J. Org. Chem., 2013)

(untitled) - Grob, K.; Zürcher, F. (J. Chromatogr. A, 1976)

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2014)

(untitled) - Kováts, E. (Helv. Chim. Acta, 1958)

(untitled) - Wang, T.; Mohr, K. I.; Stadler, M.; Dickschat, J. S. (Beilstein J. Org. Chem., 2018)

(untitled) - Dickschat, J. S.; Celik, E.; Brock, N. L. (Beilstein J. Org. Chem., 2018)

(untitled) - Wang, T.; Rabe, P.; Citron, C. A.; Dickschat, J. S. (Beilstein J. Org. Chem., 2013)

(untitled) - Dickschat, J. S.; Wang, T.; Stadler, M. (Beilstein J. Org. Chem., 2018)

(untitled) - Helaly, S. E.; Thongbai, B.; Stadler, M. (Nat. Prod. Rep., 2018)

(untitled) - Pažoutová, S.; Follert, S.; Bitzer, J.; Keck, M.; Surup, F.; Šrůtka, P.; Holuša, J.; Stadler, M. (Fungal Diversity, 2013)

(untitled) - Pouzar, Z. (Czech Mycol., 1978)

(untitled) - Mühlbauer, A.; Triebel, D.; Persoh, D.; Wollweber, H.; Seip, S.; Stadler, M. (Mycol. Progress, 2002)

(untitled) - Dickschat, J. S.; Wickel, S.; Bolten, C. J.; Nawrath, T.; Schulz, S.; Wittmann, C. (Eur. J. Org. Chem., 2010)

Identification of Essential Oil Components by Gas Chromatography/Mass Spectrometry - Adams, R. P. (Allured, 2009)

(untitled) - Southwell, I. A.; Russell, M. F.; Maddox, C. D. A.; Wheeler, G. S. (J. Chem. Ecol., 2003)

(untitled) - Kirsch, F.; Horst, K.; Röhrig, W.; Rychlik, M.; Buettner, A. (Metabolomics, 2013)

(untitled) - Wu, S.; Zorn, H.; Krings, U.; Berger, R. G. (Flavour Fragrance J., 2007)

(untitled) - Amand, S.; Langenfeld, A.; Blond, A.; Dupont, J.; Nay, B.; Prado, S. (J. Nat. Prod., 2012)

(untitled) - Barra, L.; Schulz, B.; Dickschat, J. S. (ChemBioChem, 2014)

(untitled) - Tomsheck, A. R.; Strobel, G. A.; Booth, E.; Geary, B.; Spakowicz, D.; Knighton, B.; Floerchinger, C.; Sears, J.; Liarzi, O.; Ezra, D. (Microb. Ecol., 2010)

(untitled) - Shaw, J. J.; Berbasova, T.; Sasaki, T.; Jefferson-George, K.; Spakowicz, D. J.; Dunican, B. F.; Portero, C. E.; Narváez-Trujillo, A.; Strobel, S. A. (J. Biol. Chem., 2015)

(untitled) - Lehnert, E. K.; Scott Sawyer, J.; Macdonald, T. L. (Tetrahedron Lett., 1989)

(untitled) - Dickschat, J. S.; Wenzel, S. C.; Bode, H. B.; Müller, R.; Schulz, S. (ChemBioChem, 2004)

(untitled) - Dickschat, J. S.; Zell, C.; Brock, N. L. (ChemBioChem, 2010)

(untitled) - Ndam, L. M.; Mih, A. M.; Tening, A. S.; Fongod, A. G. N.; Temenu, N. A.; Fujii, Y. (SpringerPlus, 2016)

(untitled) - Chang, C.-W.; Chang, H.-S.; Cheng, M.-J.; Liu, T.-W.; Hsieh, S.-Y.; Yuan, G.-F.; Chen, I.-S. (Chem. Biodiversity, 2014)

(untitled) - Bell, A. A.; Wheeler, M. H. (Annu. Rev. Phytopathol., 1986)

(untitled) - Citron, C. A.; Rabe, P.; Barra, L.; Nakano, C.; Hoshino, T.; Dickschat, J. S. (Eur. J. Org. Chem., 2014)

(untitled) - Wang, Q.; Yang, Y.; Zhao, X.; Zhu, B.; Nan, P.; Zhao, J.; Wang, L.; Chen, F.; Liu, Z.; Zhong, Y. (Food Chem., 2006)

(untitled) - Mirza-Aghayan, M.; Boukherroub, R.; Rahimifard, M.; Zadmard, R. (J. Iran. Chem. Soc., 2011)

(untitled) - Buccini, M.; Punch, K. A.; Kaskow, B.; Flematti, G. R.; Skelton, B. W.; Abraham, L. J.; Piggott, M. J. (Org. Biomol. Chem., 2014)

(untitled) - O’Hora, P. S.; Incerti-Pradillos, C. A.; Kabeshov, M. A.; Shipilovskikh, S. A.; Rubtsov, A. E.; Elsegood, M. R. J.; Malkov, A. V. (Chem. – Eur. J., 2015)

(untitled) - Takaya, Y.; Hotta, R.; Fujiwara, K.; Otani, R.; Uchiyama, Y.; Sakakibara, M.; Fukuda, E.; Niwa, M.; Inouye, K.; Oohata, A. A. (Org. Lett., 2014)

(untitled) - Hayashi, N.; Ding, J.; Ding, Z.; Chen, Z.; Yi, Y.; Komae, H. (Z. Naturforsch., C: J. Biosci., 1990)

(untitled) - Kuhnert, E.; Fournier, J.; Peršoh, D.; Luangsa-ard, J. J. D.; Stadler, M. (Fungal Diversity, 2014)